Personnel management : concepts and applications - Byars, Lloyd L.; Rue, Leslie W. (Philadelphia : W.B. Saunders, 1979)
Section one serves as an introduction and orientation for the book. Personnel management is defined and basic terminology is introduced. Career opportunities and future trends in personnel management are also presented. Section two deals with environmental forces and their effect on the functions of personnel management as well as those of the total organization. Section three presents topics that are related to analyzing and developing the abilities of an organization's human resources. Section four deals with encouraging and obtaining maximum effort from the work force. Section five discusses topics that relate to defining the direction of the organization's personnel, including communication, employee appraisal, the bargaining process, the disciplinary process, and career planning and development.
Includes bibliographical references and index.
ne 12/07/2018
Loans
Keywords: Personnel management